Identifikasi Jenis Buah Berdasarkan Biji Dengan Menerapkan Menerapkan Metode Viola Jones - Dessy Aina Sari; Nelly Astuti Hasibuan; Imam Saputra (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2020)
The era of technology that is increasingly developing nowadays has an influence on knowledge, one of which is the introduction or identification. The identifier is a stage in the development of an identification system with image processing and detection. In the introduction of fruit seeds, there are some people or lay people who find it difficult to distinguish the types of fruit based on the seeds of the fruit because there are several fruits that have seeds that are almost the same shape and color, so there may be errors in determining the type of fruit. To find out the type of fruit based on the seeds, he identified the seeds. This identification is done to classify in order to know the results of these types of fruit by applying the Viola Jones method which can help in identifying because the Viola Jones method is an algorithm that can detect objects in the image. In this method there are several concepts that are combined into a method so that it can detect and detect an object of the seed made. The Viola Jones method uses the Haar feature as a descriptor, then combines Integral Image and AdaBoost to find and select values and objects and form a Cascade Classifier that will be used as a detector. This identifier is useful for the community to be able to recognize or know the type of fruit through the seeds.Keywords: Image, Contraharmonic Mean Filter, Noise Reduction.